Diversion of Tourism Flows in the Asia and Pacific Region : Lessons for COVID-19 Recovery - Balasundharam, Vybhavi; Koepke, Robin (Washington, D.C. : International Monetary Fund, 2021)
The COVID-19 pandemic prompted a collapse in international tourism, severely impacting the tourism-dependent economies in the Asia and Pacific region. Once countries start reopening, tourism diversion effects could accelerate the recovery in countries that establish themselves as more attractive travel destinations than competitors. We investigate the impact of previous shocks in tourism competitor countries on visitor inflows, with a particular focus on tourism-dependent Pacific Island Countries (PICs). We find that PICs were generally resilient to external shocks and benefitted from diversion effects for certain types of shocks. For example, the share of departures from Australia to PICs increased by 12 percent during the SARS outbreak. We then derive policy implications for the post-COVID-19 revival of inbound tourism to PICs and lessons for the future.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Gambling; Recreation; Restaurants; Sports; Tourism